(3eLed GddZIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO bHjd HGH GdVGO hGdNGA heG jKdKgeG GdfGbI GdJi JQYi fGMjI JbGd JVLY GdSMGH GPG GQH HGdecGf s
(3BNQgG (B:s
(3eGRGO Yf KdGKI eKd GdjSQhY hGdjMehQ heG GTHg aSHjdg eKd GdMQa GdChd GPG cGf RjOkG hGfeG jfXQ Edi eG HYO GdjGA hgPG BNQ eLed GddZI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B193 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1604s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs